2011
DOI: 10.1353/pla.2011.0039
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning in the Library Instruction Environment: An Exploratory Study

Abstract: This paper describes an exploratory study investigating the impact of problem-based learning and clicker technology as active learning strategies at the American University of Sharjah Library, United Arab Emirates (UAE). Studies compared traditional and active learning classes. The present article maps the successes and challenges of these unique classroom encounters, and through correlation of findings from a broader educational context, considers the impact of these teaching strategies on student performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 19 publications
2
31
0
3
Order By: Relevance
“…Chat and Venezia (2009) suggest that students can be successful if entry level courses concentrated on cognitive strategies such as analyzing, reasoning, argumentation, and interpretation (Ross &Furno, 2011). The educational process is evolutionary and faculty members need to understand that technology, pedagogy, and content delivery will continue to evolve over time.…”
Section: Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Chat and Venezia (2009) suggest that students can be successful if entry level courses concentrated on cognitive strategies such as analyzing, reasoning, argumentation, and interpretation (Ross &Furno, 2011). The educational process is evolutionary and faculty members need to understand that technology, pedagogy, and content delivery will continue to evolve over time.…”
Section: Existing Literaturementioning
confidence: 99%
“…The educational process is evolutionary and faculty members need to understand that technology, pedagogy, and content delivery will continue to evolve over time. The evolutionary process will bring to fruition new learning initiatives to assist with addressing the current academically diverse classroom (Ross &Furno, 2011). In order for faculty members to take part in establishing new learning techniques, change on the faculty members' part is imperative.…”
Section: Existing Literaturementioning
confidence: 99%
“…The role of the instructor in problem-based learning is to design appropriate and sufficiently complex problems for students to solve, and to facilitate communication that encourages students to disagree, form conclusions and meet specified learning objectives (Wood, 2003). In an in-person library session, problem-based learning techniques are typically achieved through strategies of authentic assessment and active learning (Ross and Furno, 2011). In the online, asynchronous environment, the Toolkit tutorials model problem-based learning through activities.…”
Section: Principle #2: Adult-centered Instruction Is Problem Basedmentioning
confidence: 99%
“…1) while producing instructional modules of direct relevance to the university's science curriculum. Ross and Furno (2011) used clickers in the classroom to increase student participation and foster active student engagement through immediate feedback. The results were positive; the authors reported that students were "engaged and motivated" (p. 958) and that they took "responsibility for their own learning" (p. 957).…”
Section: Literature Reviewmentioning
confidence: 99%